Evaluate. Pay close attention to all brackets and signs.|4| - |-5|
a. 9
c. 1
b. -9

Answers

Answer 1
Answer: |4| - |-5|
all the absolute numbers are always positive.
when you will open the brackets positive will remain positive and negative will change to positive so we get
4 - 5
= -1 Ans
Answer 2
Answer: The answer to this equation is 9.
4-(-5)= (when there is two negative side by side, it becomes positive)
4+5=9

Related Questions

Uh, one second I got to put the picture ;-;
Nicole runs 6 miles in 45 minutes. At the same rate, how many minutes would she take to run 4 miles?
Help me please !!!!!!!!!!!!!!!!!!!!!!!!!!!!!!
Evaluate the expressions when a = 10, b = -2, and c = -5: (a) a * b (b) 10 * b² (c) -a * b² + (-c) (d) (a * c + a) / b
On a particular day, the wind added 2 miles per hour to Jaime's rate when she was rowing with the wind and subtracted 2 miles per hour from her rate on her return trip. Jaime found that in the same amount of time she could row 44 miles with the wind, she could go only 36 miles against the wind.What is her normal rowing speed with no wind?

Determine the type and number of solutions of 7x^2+3x+8=0

Answers

7x^2+3x+8=0 \n \na =7, \ b=3 ,\ c=8 \n \n\Delta =b^2 - 4ac = 3^2 -4\cdot 7\cdot 8=9-224=-215\n \n Answer : \ \Delta \ is \ negative,\ this \ gives \ two \ imaginary \ solutions


7x^2+3x+8=0\n\n \Delta=3^2-4\cdot7\cdot8=9-224=-115\ \ \Rightarrow\ \ \ no\ real\ solution\n\n\ two\ complex\ solutions\n\n\Delta=-115=115\cdot i^2\ \ \ \Rightarrow\ \ \ √(\Delta) = √(115)\ i\n\nx_1= (-b- √(\Delta) )/(2a) = (-3- √(115)\ i)/(2\cdot 7) = (-3- √(115i))/(14)\n\nx_2= (-b+ √(\Delta) )/(2a) = (-3+ √(115)\ i)/(2\cdot 7) = (-3+ √(115)\ i)/(14)

Write an algebraic expression for the following word phrase: the quotient of r and 12?

Answers

quotient= division so 12/r would be your answer 

Final answer:

The algebraic expression for the word phrase 'the quotient of r and 12' is r/12. This represents a division operation where r is divided by 12.

Explanation:

The phrase 'the quotient of r and 12' can be translated into an algebraic expression as r/12. In this expression, 'quotient' refers to the mathematical operation of division. Hence, the expression means that the variable 'r' is divided by '12'.

Learn more about Algebra here:

brainly.com/question/24875240

#SPJ2

And the last question is:The sum of two consecutive integers is at least 14. What is the least possible pair of integers?
A) 4 and 5
B) g and 7
C) 7 and 8
D) 8 and 9

Answers

It should be " b " That should be right but u may want to wait for others to respond to this to make sure
I think it is B it cannot be the others!

Given that QT is an altitude of triangle QRS, measure of angle QTS=(6x+36), and QR = 2x – 5, find QR. a. 7
b. 9
c. 11
d. 13

Answers

we know that
if QT is an altitude of triangle QRS
then
the measure of angle QTS is equal to 90°
so
6x+36=90-----> 6x=90-36----> x=54/6
x=9
QR=2x-5-----> QR=2*9-5-----> QR=18-5-----> QR=13

the answer is
QR=13

Answer: It is D. 13 on edge-nuity!


Find the equation of the circle whose center and radius are given.center ( -2, -5), radius = 1

Answers

Answer:  The required equation of the circle is x^2+y^2+4x+10y+28=0.

Step-by-step explanation:  We are given to find the equation of the circle with center (-2, -5) and radius of length 1 unit.

We know that

the standard equation of a circle with center (h, k) and radius of length r units is given by

(x-h)^2+(y-k)^2=r^2~~~~~~~~~~~~~~~~~~~~~~~~~~~~~(i)

For the given circle, we have

center, (h, k) = (-2, -5)   and  radius, r = 1 units.

Therefore, from equation (i), we get

(x-(-2))^2+(y-(-5))^2=1^2\n\n\Rightarrow (x+2)^2+(y+5)^2=1\n\n\Rightarrow x^2+4x+4+y^2+10x+25=1\n\n\Rightarrow x^2+y^2+4x+10y+29-1=0\n\n\Rightarrow x^2+y^2+4x+10y+28=0.

Thus, the required equation of the circle is x^2+y^2+4x+10y+28=0.

as i said before put the center instead of (h,k) in the general formula and put r=1 
so (x-(-2))^2 + (y-(-5)^2 = 1 
(x+2)^2 + (y+5)^2 = 1

Helpppppppppp aasapppp

Answers

Answer:

2

Step-by-step explanation:

Convert mixed fraction to improper fraction

-2(2)/(3)=-(8)/(3)\n\n\n-1(1)/(3)=-(4)/(3)

-2(2)/(3) ÷ -1(1)/(3) =(-8)/(3) ÷ -(4)/(3)

                  =-(8)/(3)*-(3)/(4)\n\n\n=2 *1 \n\n= 2

Answer:

2

Step-by-step explanation:

Simplify the following:

(-(2 + 2/3))/(-(1 + 1/3))

(-(2 + 2/3))/(-(1 + 1/3)) = (-1)/(-1)×(2 + 2/3)/(1 + 1/3) = (2 + 2/3)/(1 + 1/3):

(2 + 2/3)/(1 + 1/3)

Put 1 + 1/3 over the common denominator 3. 1 + 1/3 = 3/3 + 1/3:

(2 + 2/3)/(3/3 + 1/3)

3/3 + 1/3 = (3 + 1)/3:

(2 + 2/3)/((3 + 1)/3)

3 + 1 = 4:

(2 + 2/3)/(4/3)

Put 2 + 2/3 over the common denominator 3. 2 + 2/3 = (3×2)/3 + 2/3:

((3×2)/3 + 2/3)/(4/3)

3×2 = 6:

(6/3 + 2/3)/(4/3)

6/3 + 2/3 = (6 + 2)/3:

((6 + 2)/3)/(4/3)

6 + 2 = 8:

(8/3)/(4/3)

Multiply the numerator by the reciprocal of the denominator, (8/3)/(4/3) = 8/3×3/4:

(8×3)/(3×4)

(8×3)/(3×4) = 3/3×8/4 = 8/4:

8/4

The gcd of 8 and 4 is 4, so 8/4 = (4×2)/(4×1) = 4/4×2 = 2:

Answer: 2